Rethinking internationalization in STEM: Decolonial perspectives from U.S. broadening participation initiatives - Dabiri, Mohammadali (American Journal of STEM Education, 2026)
Internationalization in higher education is often framed as universally beneficial, yet scholars increasingly highlight its entanglement with colonial legacies and structural inequities. This study examines how equity-driven internationalization is enacted within U.S. STEM broadening participation programs led by two foreign-born women serving as principal investigators of National Science Foundation–funded initiatives. Guided by Critical Narrative Inquiry, the study draws on in-depth interviews to explore how their leadership practices challenge deficit-oriented perspectives and promote inclusive pathways for historically underrepresented students in STEM. Findings reveal that relational leadership, community accountability, and epistemic pluralism shape mentoring and program design, aligning with decolonial perspectives on internationalization.